« Ouvrez les frontières ! Ouvrez les villes ! » : L’effet paradoxal des politiques d’hébergement sur la vulnérabilité des femmes migrantes à Athènes - Alice Latouche (Université des Sciences et Technologies de Lille, 2021)
This article aims to analyze, with a gender lens, the paradoxical impact of the accommodation program ESTIA, for “vulnerable migrants” on women in exile, in the city of Athens. We shall examine the assessment procedure to reveal the gendered stereotypes of vulnerability : to enter the accommodation program, women must perform vulnerability according to the implicit expectations of social workers. To understand the ambivalence of this program, presented as a humanitarian aid and a policy for integration and accommodation, we shall then analyse what happens to the women recognized as vulnerable, at the end of the program. As it is quite difficult to find a legal employment and to rent a flat, most of them are forced to live in the streets. The study of their journey into town puts in perspective the paradox of public policies for the accommodation of “vulnerable migrants” which, by functioning through selection, exclusion and by providing only short-term solutions, reinforce the multiple relations of power that women are subjected, and their exposure to violence.